Uso da PCR de suabe conjuntival para detecção de Leishmania spp. Em gatos - De Sousa Oliveira, Trícia Maria Ferreira (2015)
The relevance of the dog as a source of visceral leishmaniasis infection is known, but the role of cats as reservoir hosts for leishmaniasis is not yet fully clear. This study assessed the efficacy of conjunctival swab PCR (CS-PCR) in the detection of cats infected by Leishmania spp. The results were seven (13.5%) cats positive for Leishmania spp. in the PCR, in 52 cats tested from Pirassunuga-SP and Ilha Solteira-SP. From the city of Pirassununga – SP 28.6% (2/7) were positive and from the city of Ilha Solteira – SP 11.1% (5/45) were positive. The results showed that CS-PCR was capable of detecting cats infected by this protozoan. Conjunctival swab samples proved easier to perform in cats, which might facilitate studies on the frequency and distribution of feline leishmaniasis.